Anti-oxidation cold-resistant knife scraping cloth and application thereof
By introducing composite flame retardants and antibacterial antioxidants into the knife scraper and forming a chemical bonded crosslinking network, the existing knife scraper’s shortcomings in flame retardant, antibacterial, anti-aging and severe cold resistance are solved, and higher performance and longer service life are achieved.
Patent Information
- Application Number
- CN202510256615.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-11
AI Technical Summary
Existing knife scrapers perform poorly in flame retardant, severe cold resistance, antibacterial and anti-aging, resulting in safety hazards, short service life and increased maintenance costs.
The first modified coating and the second modified coating are used to form a synergistic effect to improve the flame retardant performance and antibacterial antioxidant ability by the use of composite flame retardant and antibacterial antioxidant respectively, and a primary crosslinking network is formed through chemical bonding to enhance the mechanical properties.
It significantly improves the flame retardant performance, antibacterial ability, anti-aging performance and severe cold resistance of the knife scraper, making it excellent in high temperature, ultraviolet rays and severe cold environments, extending its service life and reducing maintenance costs.
Smart Images

Figure CN119800730A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of silk weaving technology, and in particular relates to an anti-oxidation and severe cold-resistant knife scraping cloth and its application. Background Art
[0002] Traditional knife-coated cloth uses high-strength polyester filament as the base cloth. After multiple rigorous process flows, polyvinyl chloride liquid PVC slurry is applied on both sides of the base cloth, and then the liquid glue is plasticized by a drying process to combine it into a whole. However, the existing knife-coated cloth still has the following defects: low flame retardancy; weak cold resistance; poor antibacterial ability; poor anti-aging ability. For example, in some public places with high fire protection requirements, such as large outdoor advertising spaces in shopping malls and exhibition halls, or knife-coated cloth used for equipment protection in industrial plants, once encountering open flames or high temperature sources, due to the flammable nature of its own material, it is very easy to burn quickly, and the fire will spread in a short time, which will not only cause damage to advertising facilities and protective equipment, but also may cause serious safety accidents, threatening the safety of surrounding personnel and property. The low antibacterial ability has become a major shortcoming that restricts the expansion of knife-coated cloth in specific fields. Take medical places, temporary facilities for isolation and protection, or dust covers in food processing workshops as examples. If ordinary knife-coated cloth is used, bacteria, molds and other microorganisms are very easy to breed and multiply on its surface. The humid environment and residual organic matter provide an ideal "breeding ground" for microorganisms. These microorganisms will not only erode the fiber structure of the scraper cloth itself and shorten its service life, but may also pollute the surrounding environment, posing a potential threat to medical and food hygiene and safety. At the same time, the scraper cloth exposed to the outdoors for a long time is subjected to high-intensity ultraviolet radiation, wind, rain, and repeated "torture" of severe cold climates. Under the continuous action of ultraviolet rays, its fiber molecular chains will gradually break, and the coating material will also age and peel off, resulting in a decrease in the strength of the scraper cloth and fading of color. The originally bright and beautiful advertising images became dim, and the heat insulation effect of the scraper cloth used for building shading was greatly reduced, which seriously affected its use effect, greatly increased the frequency of replacement, and increased the cost of use.
[0003] Therefore, providing a new formula of scraper cloth and its preparation method to solve the above-mentioned defects is an urgent problem to be solved. Summary of the invention
[0004] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide an antioxidant and severe cold-resistant scraper cloth and its application; the present application introduces the use of a first modified coating and a second modified coating in the preparation process of the scraper cloth, wherein the first modified coating is compounded with different flame retardants and utilizes the synergistic effect thereof to greatly improve the flame retardant properties of the prepared scraper cloth; at the same time, the antibacterial antioxidant in the second modified coating can form an antibacterial and antioxidant network, so that the prepared scraper cloth has excellent antibacterial and anti-aging functions; first, the second modified coating can also form a primary cross-linked network in the form of chemical bonding, thereby improving the tensile resistance, wear resistance, corrosion resistance, severe cold resistance and other properties of the prepared scraper cloth, so that the prepared scraper cloth has excellent quality and long service life.
[0005] To achieve the above object, the present invention provides the following technical solutions: An anti-oxidation and severe cold-resistant scraper cloth comprises, from inside to outside, a base layer, a first modified coating layer, a second modified coating layer and a surface layer; The first modified coating comprises the following components by mass: 100-120 parts of modified epoxy resin, 20-30 parts of nano titanium dioxide, 10-15 parts of triethyl phosphate, 5-10 parts of ammonium polyphosphate, 1-5 parts of curing agent, and 0.1-0.5 parts of thickener; The second modified coating comprises the following components by mass: 80-100 parts of polyurethane acrylic resin, 10-15 parts of antibacterial antioxidant, 1-3 parts of 1-hydroxycyclohexyl phenyl ketone, 1-3 parts of dibutyl phthalate, 0.5-1 parts of dioctyl sebacate, 1-3 parts of curing agent, and 0.5-1 parts of thickener; The surface layer comprises the following components by weight: 60-80 parts of water-based fluorocarbon resin and 0.5-1.5 parts of leveling agent.
[0006] Preferably, the modified epoxy resin is prepared by the following steps: S11. Mix the epoxy resin and acetone in a mass ratio of 1:5-8 and stir for 40-50 minutes until the epoxy resin is completely dissolved in the acetone to form a uniform solution; S12. Slowly add ethylenediamine and triethylamine to the solution obtained in S11, and continue stirring for 5-10 min to ensure that the reactants are evenly mixed; S13. The solution obtained in S12 is heated to 40-50°C and maintained at the temperature for 3-4h, then heated to 60-80°C and maintained at the temperature for 1-2h; S14. The solution treated in step S13 is distilled to remove the solvent to obtain the modified epoxy resin.
[0007] Preferably, the mass ratio of the ethylenediamine to the epoxy resin is 1.2-1.3:1; the mass ratio of the triethylamine to the epoxy resin is 0.01-0.05:1.
[0008] Preferably, the antibacterial antioxidant is prepared by the following steps: S21. Disperse 10-12 parts of ZIF-8 in 60-80 parts of dichloromethane by mass, add 20-25 parts of toluene-2,4-diisocyanate and stir for 1-4h, remove the solvent to obtain isocyanate-modified ZIF-8; S22. After isocyanate-modified ZIF-8, tris(2,4-di-tert-butylphenyl)phosphite and triphenyl phosphite are mixed and stirred evenly in a mass ratio of 1:1-3:1-5, the mixture is placed under a vacuum condition of 0.1-5 Pa and allowed to stand for 2-3 hours, centrifuged, washed and dried to obtain the antibacterial antioxidant.
[0009] Preferably, the curing agent in the first modified coating and the second modified coating is an isocyanate curing agent.
[0010] Preferably, the thickener in the first modified coating and the second modified coating is an alkali-swellable acrylic thickener.
[0011] Preferably, the leveling agent in the surface layer is a silicone leveling agent.
[0012] Preferably, the base layer is a biaxial warp knitted base fabric.
[0013] Preferably, the scraper cloth is prepared by the following steps: S1. Ingredients: weigh the components in proportion and prepare the slurry of the first modified coating, the second modified coating and the surface layer; S2. Scraping the first modified coating: unwind the biaxial warp knitted base fabric, heat the slurry of the first modified coating to 130-140°C, apply sizing to both sides of the biaxial warp knitted base fabric with a scraper, cool, so that both sides of the base fabric layer are bonded with the first modified coating, keep warm at 160-170°C, the thickness of the first modified coating is 0.5-0.8mm; S3. Applying the second modified coating: heating the slurry of the second modified coating to 120-130°C, applying the slurry to both sides of the first modified coating with a scraper, cooling so that both sides of the first modified coating are bonded to the second modified coating, and keeping the temperature at 140-150°C. The thickness of the second modified coating is 0.4-0.6 mm; S4. Surface scraping: prepare the surface slurry in proportion, heat the surface slurry to 110-120° C. and apply it on the surface of the double-sided second modified coating to obtain the antioxidant and severe cold-resistant scraping cloth.
[0014] An application of the antioxidant and severe cold-resistant scraping cloth in the field of outdoor advertising.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The first modified coating can greatly improve the flame retardant properties of the prepared scraper cloth by using a combination of different flame retardants and utilizing their synergistic effects; the composite flame retardant can form a dense and stable carbon layer on the surface of the scraper cloth during combustion, which plays a heat-insulating role and prevents heat transfer; nano-titanium dioxide enhances the carbon-forming ability and promotes the formation of the carbon layer, while triethyl phosphate and ammonium polyphosphate enhance the stability and density of the carbon layer by forming phosphate esters; the composite flame retardant produces a large amount of non-flammable gas when decomposed at high temperature, diluting the oxygen concentration and inhibiting the combustion of the scraper cloth; triethyl phosphate, as a phosphorus source, releases phosphate free radicals during pyrolysis, reacts with polymer chains to form phosphate esters, and enhances the stability of the carbon layer. As an intumescent flame retardant, ammonium polyphosphate decomposes to produce polyphosphoric acid during pyrolysis, which reacts with nano-titanium dioxide to form titanium pyrophosphate, enhancing the thermal insulation effect of the carbon layer; 2. The present invention enhances the dispersibility and stability of the antibacterial antioxidant by adsorbing tris(2,4-di-tert-butylphenyl)phosphite and triphenyl phosphite in the pores of ZIF-8, thereby achieving effective regulation of active sites; at the same time, when the two phosphates are released under specific conditions, the pores of ZIF-8 are liberated, thereby increasing the number of active sites; this design not only improves the antioxidant properties of the material, but also enhances its antibacterial activity. On the one hand, the released phosphates can capture free radicals, prevent the aging and cracking of the scraper cloth, and improve the thermal stability and aging resistance of the material. On the other hand, after the pores of ZIF-8 are released, the active sites inside it are exposed, and these sites can react with the amino acid residues on the bacterial cell wall, destroy the bacterial structure, and enhance the antibacterial effect. At the same time, the photocatalytic activity of ZIF-8 is also improved, and photogenerated electrons are generated through the charge transfer between the ligand and the metal to form active oxygen species, which further oxidize the pathogenic bacteria, which makes the prepared scraper cloth have excellent antibacterial and anti-aging functions; 3. The present invention introduces a resin matrix with excellent cold resistance into the first and second modified coatings and the surface layer. At the same time, the first and second modified coatings can also form a primary cross-linked network in the form of chemical bonding, thereby further improving the tensile resistance, wear resistance, corrosion resistance, cold resistance and other properties of the prepared scraper cloth, so that the prepared scraper cloth has excellent quality and long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The present invention is a flow chart of the process for preparing the antioxidant and severe cold-resistant scraper cloth; Figure 2 The present invention is a process flow chart for preparing the modified epoxy resin; Figure 3 The present invention is a flow chart of the preparation process of the antibacterial antioxidant. DETAILED DESCRIPTION
[0017] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] See also Figure 1-3 , the present invention provides a technical solution: Example
[0019] A method for preparing an antioxidant and severe cold-resistant scraping cloth: S1. Ingredients: weigh the components in proportion and prepare the slurry of the first modified coating, the second modified coating and the surface layer; S2. Scraping the first modified coating: unwind the biaxial warp knitted base fabric, heat the slurry of the first modified coating to 130°C, apply sizing to both sides of the biaxial warp knitted base fabric with a scraper, cool, so that both sides of the base fabric layer are bonded with the first modified coating, keep warm at 160°C for 1h, the thickness of the first modified coating is 0.5mm; S3. Applying the second modified coating: heating the slurry of the second modified coating to 120°C, applying slurry to both sides of the first modified coating with a scraper, cooling so that both sides of the first modified coating adhere to the second modified coating, and keeping the temperature at 140°C for 1h. The thickness of the second modified coating is 0.4mm. S4. Surface scraping: prepare the surface slurry in proportion, heat the surface slurry to 110° C. and apply it on the surface of the double-sided second modified coating to obtain the scraping cloth with high strength, antibacterial and antioxidant functions.
[0020] The first modified coating comprises the following components: Components Dosage (100g / portion) Modified epoxy resin 100 copies Nano Titanium Dioxide 20 servings Triethyl phosphate 10 servings Ammonium Polyphosphate 5 servings Curing agent 2 servings Thickener 0.1 part The curing agent is hexamethylene diisocyanate; The thickener is an alkali-swellable acrylic thickener, specifically BASF Rheovis® AS 1130; The modified epoxy resin is prepared by the following method (where 100 g is fixed as one unit mass part): S11. 120 parts of epoxy resin and 600 parts of acetone were mixed and stirred for 40 min until the epoxy resin was completely dissolved in acetone to form a uniform solution; S12. 144 parts of ethylenediamine and 1.2 parts of triethylamine were slowly added to the solution obtained in S11, and stirring was continued for 5 min to ensure that the reactants were evenly mixed; S13. The solution obtained in S12 was heated to 40°C and maintained at this temperature for 3 hours, and then heated to 60°C and maintained at this temperature for 1 hour; S14. The solution treated in step S13 is distilled to remove the solvent to obtain the modified epoxy resin.
[0021] The epoxy resin was purchased from Hubei Zhenzhengfeng New Materials Co., Ltd., and the specific brand is MF-3285.
[0022] The second modified coating comprises the following components: Components Dosage (100g / portion) Polyurethane acrylic resin 80 servings Antimicrobial Antioxidant 10 servings 1-Hydroxycyclohexylphenyl ketone 1 serving Dibutyl phthalate 1 serving Dioctyl Sebacate 0.5 serving Curing agent 1 serving Thickener 0.5 serving The grade of the polyurethane acrylic resin is BASF Laromer PR 9000; The curing agent is hexamethylene diisocyanate; The thickener is an alkali-swellable acrylic thickener, specifically BASF Rheovis® AS 1130; The antibacterial antioxidant is prepared by the following method (where 100 g is fixed as one unit mass portion): S21. Dispersing 10 parts of ZIF-8 in 60 parts of dichloromethane, adding 20 parts of toluene-2,4-diisocyanate and stirring for 1 hour, removing the solvent to obtain isocyanate-modified ZIF-8; S22. After 10 parts of isocyanate-modified ZIF-8, 20 parts of tris(2,4-di-tert-butylphenyl)phosphite and 20 parts of triphenyl phosphite are mixed and stirred evenly, the mixture is placed under a vacuum condition of 5 Pa and allowed to stand for 2 hours, centrifuged, washed and dried to obtain the antibacterial antioxidant.
[0023] The surface layer comprises the following components: Components Dosage (100g / portion) Water-based fluorocarbon resin 60 servings Leveling agent 0.5 serving The grade of the water-based fluorocarbon resin is XPH838; The leveling agent is a silicone leveling agent, specifically HY-400.
[0024] Example 2 A method for preparing a scraper cloth with high strength, antibacterial and antioxidant functions: S1. Ingredients: weigh the components in proportion and prepare the slurry of the first modified coating, the second modified coating and the surface layer; S2. Scraping the first modified coating: unwind the biaxial warp knitted base fabric, heat the slurry of the first modified coating to 140°C, apply sizing to both sides of the biaxial warp knitted base fabric with a scraper, cool, so that both sides of the base fabric layer are bonded with the first modified coating, keep warm at 170°C for 1h, the thickness of the first modified coating is 0.5mm; S3. Applying the second modified coating: heating the slurry of the second modified coating to 130°C, applying slurry to both sides of the first modified coating with a scraper, cooling so that both sides of the first modified coating adhere to the second modified coating, and keeping the temperature at 150°C for 1h. The thickness of the second modified coating is 0.4mm. S4. Surface scraping: prepare the surface slurry in proportion, heat the surface slurry to 120° C. and apply it on the surface of the double-sided second modified coating to obtain the scraping cloth with high strength, antibacterial and antioxidant functions.
[0025] The first modified coating comprises the following components: Components Dosage (100g / portion) Modified epoxy resin 120 servings Nano Titanium Dioxide 30 servings Triethyl phosphate 15 servings Ammonium Polyphosphate 10 servings Curing agent 3 servings Thickener 0.3 parts The curing agent is hexamethylene diisocyanate; The thickener is an alkali-swellable acrylic thickener, specifically BASF Rheovis® AS 1130; The modified epoxy resin is prepared by the following method (where 100 g is fixed as one unit mass part): S11. 120 parts of epoxy resin and 600 parts of acetone were mixed and stirred for 40 min until the epoxy resin was completely dissolved in acetone to form a uniform solution; S12. 144 parts of ethylenediamine and 1.2 parts of triethylamine were slowly added to the solution obtained in S11, and stirring was continued for 5 min to ensure that the reactants were evenly mixed; S13. The solution obtained in S12 was heated to 40°C and maintained at this temperature for 4 hours, and then heated to 60°C and maintained at this temperature for 1 hour; S14. The solution treated in step S13 is distilled to remove the solvent to obtain the modified epoxy resin.
[0026] The epoxy resin was purchased from Hubei Zhenzhengfeng New Materials Co., Ltd., and the specific brand is MF-3285.
[0027] The second modified coating comprises the following components: Components Dosage (100g / portion) Polyurethane acrylic resin 100 copies Antimicrobial Antioxidant 15 servings 1-Hydroxycyclohexylphenyl ketone 1 serving Dibutyl phthalate 3 servings Dioctyl Sebacate 1 serving Curing agent 2 servings Thickener 0.5 serving The grade of the polyurethane acrylic resin is BASF Laromer PR 9000; The curing agent is hexamethylene diisocyanate; The thickener is an alkali-swellable acrylic thickener, specifically BASF Rheovis® AS 1130; The antibacterial antioxidant is prepared by the following method (where 100 g is fixed as one unit mass portion): S21. Dispersing 15 parts of ZIF-8 in 70 parts of dichloromethane, adding 25 parts of toluene-2,4-diisocyanate and stirring for 1 hour, removing the solvent to obtain isocyanate-modified ZIF-8; S22. After 15 parts of isocyanate-modified ZIF-8, 30 parts of tris(2,4-di-tert-butylphenyl)phosphite and 30 parts of triphenyl phosphite are mixed and stirred evenly, the mixture is placed under a vacuum condition of 5 Pa and allowed to stand for 2.5 hours, centrifuged, washed and dried to obtain the antibacterial antioxidant.
[0028] The surface layer comprises the following components: Components Dosage (100g / portion) Water-based fluorocarbon resin 65 servings Leveling agent 0.5 serving The grade of the water-based fluorocarbon resin is XPH838; The leveling agent is a silicone leveling agent, specifically HY-400.
[0029] Example 3 A method for preparing a scraper cloth with high strength, antibacterial and antioxidant functions: S1. Ingredients: weigh the components in proportion and prepare the slurry of the first modified coating, the second modified coating and the surface layer; S2. Scraping the first modified coating: unwind the biaxial warp knitted base fabric, heat the slurry of the first modified coating to 140°C, apply sizing to both sides of the biaxial warp knitted base fabric with a scraper, cool, so that both sides of the base fabric layer are bonded with the first modified coating, keep warm at 170°C for 1h, the thickness of the first modified coating is 0.5mm; S3. Applying the second modified coating: heating the slurry of the second modified coating to 130°C, applying slurry to both sides of the first modified coating with a scraper, cooling so that both sides of the first modified coating adhere to the second modified coating, and keeping the temperature at 150°C for 1h. The thickness of the second modified coating is 0.4mm. S4. Surface scraping: prepare the surface slurry in proportion, heat the surface slurry to 120° C. and apply it on the surface of the double-sided second modified coating to obtain the scraping cloth with high strength, antibacterial and antioxidant functions.
[0030] The first modified coating comprises the following components: Components Dosage (100g / portion) Modified epoxy resin 110 copies Nano Titanium Dioxide 25 servings Triethyl phosphate 13 servings Ammonium Polyphosphate 8 servings Curing agent 3 servings Thickener 0.3 parts The curing agent is hexamethylene diisocyanate; The thickener is an alkali-swellable acrylic thickener, specifically BASF Rheovis® AS 1130; The modified epoxy resin is prepared by the following method (where 100 g is fixed as one unit mass part): S11. 120 parts of epoxy resin and 720 parts of acetone were mixed and stirred for 40 min until the epoxy resin was completely dissolved in acetone to form a uniform solution; S12. 144 parts of ethylenediamine and 6 parts of triethylamine were slowly added to the solution obtained in S11, and stirring was continued for 5 min to ensure that the reactants were evenly mixed; S13. The solution obtained in S12 was heated to 40°C and maintained at this temperature for 4 hours, and then heated to 60°C and maintained at this temperature for 1 hour; S14. The solution treated in step S13 is distilled to remove the solvent to obtain the modified epoxy resin.
[0031] The epoxy resin was purchased from Hubei Zhenzhengfeng New Materials Co., Ltd., and the specific brand is MF-3285.
[0032] The second modified coating comprises the following components: Components Dosage (100g / portion) Polyurethane acrylic resin 90 servings Antimicrobial Antioxidant 12 servings 1-Hydroxycyclohexylphenyl ketone 1.5 servings Dibutyl phthalate 3 servings Dioctyl Sebacate 1 serving Curing agent 2 servings Thickener 0.5 serving The grade of the polyurethane acrylic resin is BASF Laromer PR 9000; The curing agent is hexamethylene diisocyanate; The thickener is an alkali-swellable acrylic thickener, specifically BASF Rheovis® AS 1130; The antibacterial antioxidant is prepared by the following method (where 100 g is fixed as one unit mass portion): S21. Dispersing 12 parts of ZIF-8 in 70 parts of dichloromethane, adding 25 parts of toluene-2,4-diisocyanate and stirring for 1 hour, removing the solvent to obtain isocyanate-modified ZIF-8; S22. After 12 parts of isocyanate-modified ZIF-8, 24 parts of tris(2,4-di-tert-butylphenyl)phosphite and 48 parts of triphenyl phosphite are mixed and stirred evenly, the mixture is placed under a vacuum condition of 5 Pa and allowed to stand for 2.5 hours, centrifuged, washed and dried to obtain the antibacterial antioxidant.
[0033] The surface layer comprises the following components: Components Dosage (100g / portion) Water-based fluorocarbon resin 70 servings Leveling agent 1 serving The grade of the water-based fluorocarbon resin is XPH838; The leveling agent is a silicone leveling agent, specifically HY-400.
[0034] Comparative Example Comparative Example 1: Comparative Example 1 is different from Example 1 in that the first modified coating originally present in Example 1 is omitted in Comparative Example 1, thereby omitting the use of triethyl phosphate and ammonium polyphosphate, and the remaining steps are exactly the same in Comparative Example 1 and Example 1.
[0035] Comparative Example 2: Comparative Example 2 is different from Example 1 in that the second modified coating originally present in Example 1 is omitted in Comparative Example 2, thereby omitting the use of antibacterial antioxidants, and the remaining steps are exactly the same in Comparative Example 2 and Example 1.
[0036] Comparative Example 3: Comparative Example 3 is different from Example 1 in that the preparation method of the antibacterial antioxidant originally present in Example 1 is omitted in Comparative Example 3, so that only untreated ZIF-8 material is added in Comparative Example 2, and the remaining steps are exactly the same in Comparative Example 3 and Example 1.
[0037] Comparative Example 4: Comparative Example 4 is different from Example 1 in that the first modified coating and the second modified coating in Example 1 are omitted in Comparative Example 4, thereby omitting the use of triethyl phosphate, ammonium polyphosphate, and antibacterial antioxidants. The remaining steps are exactly the same in Comparative Example 4 and Example 1.
[0038] Comparative Example 5: Comparative Example 5 is different from Example 1 in that the first modified coating originally present in Example 1 is omitted in Comparative Example 5, so that the epoxy resin modification treatment is not performed in Comparative Example 5, and the remaining steps are exactly the same in Comparative Example 5 and Example 1.
[0039] The scraper cloths prepared in Examples 1-3 and Comparative Examples 1-5 were tested for their warp and weft tensile load according to GB / T1040.3-2006, their warp and weft tearing load according to HG / T2581.1-2009, and their peeling load according to GB / T8808-1988. The test results are as follows:
[0040] The flame retardant properties of the scraper cloths prepared in Examples 1-3 and Comparative Examples 1 and 4 were tested according to GB / T 5455-2014. The test results are as follows:
[0041] The anti-UV aging performance of the scraper cloths prepared in Examples 1-3 and Comparative Examples 2, 3, and 4 was tested according to GB / T 1865-2009. The test results are as follows: Group Anti-UV aging performance Example 1 After 70 days, there will be slight fading, brittleness and stickiness Example 2 No obvious fading, brittleness or stickiness after 90 days Example 3 Slight fading after 75 days Comparative Example 2 After 20 days, there will be obvious fading, brittleness and stickiness. Comparative Example 3 After 40 days, it will fade, become slightly brittle and sticky. Comparative Example 4 After 20 days, there will be obvious fading, brittleness and stickiness. The cold-resistant performance of the scraper cloths prepared in Examples 1-3 was tested according to FZ / T01007-2008, and the test results are as follows: Group Low temperature resistance (-40℃) Example 1 No cracks Example 2 No cracks Example 3 No cracks Referring to the HG / T 3950-2007 standard, Staphylococcus aureus and Escherichia coli were used as sample bacteria to conduct antibacterial tests on Examples 1-3 and Comparative Examples 2, 3, and 4. The test results are as follows:
[0042] Referring to the test data of Examples 1-3, it can be seen that the antioxidant and severe cold-resistant scraper cloth provided by the present invention has a tensile load higher than 2200N / 5cm (radial) and 2000N / 5cm (weft); a tear load higher than 490N (radial) and 450N (weft); a peel load higher than 50N / 5cm (radial) and 58N / 5cm (weft), and has excellent mechanical properties; and compared with the test data of Comparative Example 5, the mechanical properties of Examples 1-3 are significantly better than those of Comparative Example 5, which strongly proves that the present application forms a primary cross-linked network in the form of chemical bonding through the first and second modified coatings, thereby improving the tensile and peeling properties of the scraper cloth. and other mechanical properties; at the same time, compared with comparative examples 1 and 4, the flame retardant properties of embodiments 1-3 are significantly better than those of comparative examples 1 and 4. This is because the composite flame retardant can form a dense and stable carbon layer on the surface of the scraper cloth during combustion, which plays a heat-insulating role and prevents heat transfer; nano-titanium dioxide enhances the carbonization ability and promotes the formation of the carbon layer, while triethyl phosphate and ammonium polyphosphate enhance the stability and density of the carbon layer by forming phosphate esters; the composite flame retardant produces a large amount of non-flammable gas when decomposed at high temperature, which dilutes the oxygen concentration and inhibits the combustion of the scraper cloth; triethyl phosphate, as a phosphorus source, releases phosphate free radicals during the pyrolysis process, reacts with the polymer chain to form phosphate esters, and enhances the stability of the carbon layer. As an intumescent flame retardant, ammonium polyphosphate decomposes during pyrolysis to produce polyphosphoric acid, which reacts with nano-titanium dioxide to form titanium pyrophosphate, thereby enhancing the thermal insulation effect of the carbon layer. In comparative examples 1 and 4, only nano-titanium dioxide plays a flame retardant role as an inorganic flame retardant, making its flame retardant effect significantly inferior to that of Examples 1-3. The severe cold resistance test data of Examples 1-3 show that the scraper cloth prepared by the invention has excellent severe cold resistance. Furthermore, the results of the UV aging resistance and antibacterial tests prove that the present invention enhances the dispersibility and stability of the antibacterial antioxidant by adsorbing tris(2,4-di-tert-butylphenyl)phosphite and triphenyl phosphite in the pores of ZIF-8, thereby achieving effective regulation of the active sites. At the same time, when the two phosphates are released under specific conditions, the pores of ZIF-8 are liberated, thereby increasing the number of active sites. This design not only improves the antioxidant properties of the material, but also enhances its antibacterial activity, so that the scraper cloth prepared by the present application has excellent antibacterial and anti-aging functions.
[0043] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An anti-oxidation and severe cold-resistant scraper cloth, characterized in that: From inside to outside, they are base layer, first modified coating layer, second modified coating layer and surface layer; The first modified coating comprises the following components by mass: 100-120 parts of modified epoxy resin, 20-30 parts of nano titanium dioxide, 10-15 parts of triethyl phosphate, 5-10 parts of ammonium polyphosphate, 1-5 parts of curing agent, and 0.1-0.5 parts of thickener; The second modified coating comprises the following components by mass: 80-100 parts of polyurethane acrylic resin, 10-15 parts of antibacterial antioxidant, 1-3 parts of 1-hydroxycyclohexyl phenyl ketone, 1-3 parts of dibutyl phthalate, 0.5-1 parts of dioctyl sebacate, 1-3 parts of curing agent, and 0.5-1 parts of thickener; The surface layer comprises the following components by weight: 60-80 parts of water-based fluorocarbon resin and 0.5-1.5 parts of leveling agent.
2. The anti-oxidation and severe cold-resistant scraper cloth according to claim 1, characterized in that: The modified epoxy resin is prepared by the following steps: S11. Mix the epoxy resin and acetone in a mass ratio of 1:5-8 and stir for 40-50 minutes until the epoxy resin is completely dissolved in the acetone to form a uniform solution; S12. Slowly add ethylenediamine and triethylamine to the solution obtained in S11, and continue stirring for 5-10 min to ensure that the reactants are evenly mixed; S13. The solution obtained in S12 is heated to 40-50°C and maintained at the temperature for 3-4h, then heated to 60-80°C and maintained at the temperature for 1-2h; S14. The solution treated in step S13 is distilled to remove the solvent to obtain the modified epoxy resin.
3. The anti-oxidation and severe cold-resistant scraper cloth according to claim 2, characterized in that: The mass ratio of the ethylenediamine to the epoxy resin is 1.2-1.3:1; the mass ratio of the triethylamine to the epoxy resin is 0.01-0.05:
1.
4. The anti-oxidation and severe cold-resistant scraper cloth according to claim 1, characterized in that: The antibacterial antioxidant is prepared by the following steps: S21. Disperse 10-12 parts of ZIF-8 in 60-80 parts of dichloromethane by mass, add 20-25 parts of toluene-2,4-diisocyanate and stir for 1-4h, remove the solvent to obtain isocyanate-modified ZIF-8; S22. After isocyanate-modified ZIF-8, tris(2,4-di-tert-butylphenyl)phosphite and triphenyl phosphite are mixed and stirred evenly in a mass ratio of 1:1-3:1-5, the mixture is placed under a vacuum condition of 0.1-5 Pa and allowed to stand for 2-3 hours, centrifuged, washed and dried to obtain the antibacterial antioxidant.
5. The anti-oxidation and severe cold-resistant scraper cloth according to claim 1, characterized in that: The curing agent in the first modified coating and the second modified coating is an isocyanate curing agent.
6. The anti-oxidation and severe cold-resistant scraper cloth according to claim 1, characterized in that: The thickener in the first modified coating and the second modified coating is an alkali swellable acrylic thickener.
7. The anti-oxidation and severe cold-resistant scraper cloth according to claim 1, characterized in that: The leveling agent in the surface layer is an organic silicon leveling agent.
8. The anti-oxidation and severe cold-resistant scraper cloth according to claim 1, characterized in that: The base layer is a biaxial warp knitted base fabric.
9. The anti-oxidation and severe cold-resistant scraper cloth according to claim 1, characterized in that: The knife scraper cloth is prepared by the following steps: S1. Ingredients: weigh the components in proportion and prepare the slurry of the first modified coating, the second modified coating and the surface layer; S2. Scraping the first modified coating: unwind the biaxial warp knitted base fabric, heat the slurry of the first modified coating to 130-140°C, apply sizing to both sides of the biaxial warp knitted base fabric with a scraper, cool, so that both sides of the base fabric layer are bonded with the first modified coating, keep warm at 160-170°C, the thickness of the first modified coating is 0.5-0.8mm; S3. Applying the second modified coating: heating the slurry of the second modified coating to 120-130°C, applying the slurry to both sides of the first modified coating with a scraper, cooling so that both sides of the first modified coating are bonded to the second modified coating, and keeping the temperature at 140-150°C. The thickness of the second modified coating is 0.4-0.6 mm; S4. Surface scraping: prepare the surface slurry in proportion, heat the surface slurry to 110-120° C. and apply it on the surface of the double-sided second modified coating to obtain the antioxidant and severe cold-resistant scraping cloth.
10. Use of the antioxidant and severe cold-resistant scraper cloth according to any one of claims 1 to 9 in the field of outdoor advertising.